Integration of Blockchain-Based Smart Contracts in the Resolution of Commercial Contract Disputes - Warmiyana Zairi Absi; Rika Mulyati; Sinung Suakanto (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of blockchain technology encourages the use of smart contracts as digital contract instruments that are automatic and cannot be changed, especially in cross-sector commercial transactions. This study aims to analyze the legal status of blockchain-based smart contracts as well as evaluate the possibility of their integration in legally recognized commercial contract dispute resolution mechanisms. This research uses a normative legal research method with a conceptual and case legislation approach conducted through a literature study of laws and regulations, legal doctrine, as well as relevant decisions and cases. This study does not involve respondents or informants because it focuses on the analysis of legal norms and concepts. The data was analyzed qualitatively juridically through interpretation methods and legal arguments. The results of the study show that smart contracts can in principle be integrated in the settlement of commercial contract disputes as an instrument for the implementation and proof of contracts, but have not been able to fully replace the role of conventional dispute resolution mechanisms due to their limitations in handling legal interpretation, the application of the principle of good faith, and certain conditions such as non-technical defaults. This study concludes that the integration of smart contracts requires a hybrid model that combines technology-based automated execution with a law-based dispute resolution mechanism to ensure legal certainty and substantive justice in commercial contract practice.